1985
DOI: 10.1212/wnl.35.12.1776
|View full text |Cite
|
Sign up to set email alerts
|

Adult metachromatic leukodystrophy

Abstract: The visual and somatosensory evoked potentials were delayed in two cases of the adult form of metachromatic leukodystrophy. Brainstem auditory evoked potentials were normal. The conduction velocity along peripheral nerves was 50% slowed in one case and near normal in the other. The findings are compatible with demyelination in the central and peripheral nervous systems. The diagnosis of metachromatic leukodystrophy should be considered in cases of early dementia, with or without psychosis or other neurologic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

1992
1992
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 0 publications
0
8
1
Order By: Relevance
“…8,22 There are rare reports of multifocal conduction slowing in MLD, but they relate mostly to the adult form. 7,12,35 In 1 case of early juvenile MLD, the initial NCS at 4 years of age revealed nonuniform slowing in distal and proximal segments of the ulnar and peroneal nerves, with differences of 28 and 19 m/s, respectively. 25 The velocities were uniformly slow in a follow-up study 20 months later.…”
Section: Discussionmentioning
confidence: 97%
“…8,22 There are rare reports of multifocal conduction slowing in MLD, but they relate mostly to the adult form. 7,12,35 In 1 case of early juvenile MLD, the initial NCS at 4 years of age revealed nonuniform slowing in distal and proximal segments of the ulnar and peroneal nerves, with differences of 28 and 19 m/s, respectively. 25 The velocities were uniformly slow in a follow-up study 20 months later.…”
Section: Discussionmentioning
confidence: 97%
“…In Pelizaeus-Merzbacher disease (PMD), Logan and Taylor found delayed VEPs and an absent central response on SEP. In metachromatic leukodystrophy (MLD), WuljJand Trojaborg (11) found abnormal VEPs and SERs but normal auditory evoked responses in two cases of MLD, a finding supported by Logan and Taylor (7). These authors also reported four patients with mixed sulfatase deficiency in whom the auditory evoked responses and SERs were abnormal or absent but the VEPs were normal.…”
Section: Jjv/divmentioning
confidence: 75%
“…Wulff et al. (9) have reported a patient with normal NCVs, but she had abnormal sensory action potentials suggesting a partial block or slowing in conduction velocity. There are adult and infantile MLD patients reported in the literature who had the clinical pattern of isolated peripheral neuropathy (10–12).…”
Section: Discussionmentioning
confidence: 99%